EFFICACY OF CASE BASED LEARNING IN UNDERSTANDING PHYSIOLOGY OF ERYTHROCYTES - Dr. Sangeeta Abhay Patil (EPRA International Journal of Research and Development (IJRD), 2023)
Physiology is the subject taught away from clinical setting. Therefore the students fail to connect the subject taught through didactic lectures to the clinical courses. Case based learning can be used in conjunction with didactic lectures to help the students for better understanding and application of Physiology with clinical correlation. The aim is to study efficacy of case based learning in understanding of Physiology of erythrocytes. Objective to introduce Case Based Learning which is student centric and facilitates the student to be lifelong learners and enhancing their understanding of physiology. Physiology of erythrocytes was taught to all the first year Homoeopathic students through didactic lectures. The concept of case based learning was introduced to the students. A MCQ test formulated on erythrocyte physiology was taken before introducing the paper based cases to the students. After the students have solved the paper based cases in groups same MCQ test was repeated. The performance of pre and post introduction of case based learning was analyzed. The student’s perception was collected on basis of questionnaires. The graph of pre and post- test shows a significant improvement in understanding of physiology of erythrocytes. It is evident from the analysis of the feedback percentage of the students agreeing to the effectiveness of case based learning of erythrocytes ranges from 57 to 82 percent. Case based learning sessions can be judiciously used to enhance the understanding of Physiology and its application in Homoeopathic students.